Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Pengawasan Terhadap Kinerja Pegawai (Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Malang) - Arie Dzulhijjah; Hadi Sunaryo; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted at the Human Resources Development and Human Resources Development Agency (BKPSDM) of Malang City. The purpose of this study is to examine and analyze the influence of the work environment, work discipline and supervision on the performance of employees of the Human Resources and Human Resources Development Agency (BKPSDM) Malang.The variables used are the work environment, work discipline and supervision as independent variables, while the employee performance variable is the dependent variable.The sampl used in this study was 44 employees, using quantitative methods. Data collection methods by collecting primary and secondary data. The anlysus used includes instrument testing, classic assumption tests, normality tests, multiple linear regession, hypothesis testing and coefficient of determination test using multiple regression analysis using SPSS 26 for Windows software.The results showed that the variables of work environment, work discipline and supervision had a simultaneous or partial effect on employee performance.Keywords: Work environment, work discipline, supervision, performance.